1988
DOI: 10.1111/j.1600-0773.1988.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Absorption of Inorganic Mercury from Rat Small Intestine. I. Solvent Drag Effect on Absorption of Inorganic Mercury

Abstract: A correlation of mercury absorption with water absorption was investigated by using the perfusion of rat small intestine with buffers containing 10(-4) M HgCl2. With a decrease in the osmolarity of the buffers or with increases in the sodium ion and urea concentrations in the buffers, absorption of water and mercury and accumulation of mercury in the intestinal tissue increased, and the increases in mercury absorption and accumulation were found to correlate with the increase in water absorption. Both the decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In our previous report (Endo et al 1988a), the absorption of HgC12 rose with an increase in water absorption and decreased with an increase in water secretion. It has been suggested that HgCl, was absorbed with water through the pores of the brush border membrane (solvent drag).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In our previous report (Endo et al 1988a), the absorption of HgC12 rose with an increase in water absorption and decreased with an increase in water secretion. It has been suggested that HgCl, was absorbed with water through the pores of the brush border membrane (solvent drag).…”
mentioning
confidence: 60%
“…Isotonic phosphate buffers at pH 5.5, 6.4 and 7.4 containing NaCl (PBS) or mannitol (PBM) were used. PBS and PBM at three pHs were the same buffers termed as buffer systems-I and -11 in the previous report (Endo et al 1988a), respectively. HgCI, and some agents were added to PBS and PBM, just before experiments.…”
Section: Methodsmentioning
confidence: 99%
“…PBS at these pHvalues contained 147.2, 148.7 and 145.4 mM of NaCI, respectively, and PBM correspondingly contained 274, 276 and 270 mM of mannitol. PBS and PBM are the same buffers termed buffer systems-I and -11 in the previous report (Endo et al 1988a), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Methyl mercuric chloride and phenyl mercuric chloride were obtained from Nakarai Chemicals, Ltd. and Merck Co., respectively. The isotonic phosphate buffered salines of pH 5.5, 6.4 and 7.4 (about 310 mOsM) were the same buffers as buffer-system-I in the previous report (Endo et al 1988a). The structu-a1 formulas and abbreviations of the organic mercuric compounds used were listed in fig.…”
Section: Methodsmentioning
confidence: 99%
“…From the chemical properties of HgC1, (Webb 1966;Hahne & Kroontje 1973;Gutknecht 1981;Bienvenue et al 1984), the existing forms of HgCl, in the media depend mainly on the relative concentrations of OH-and C1-. On the other hand, the increase in water absorption increased the absorption of HgCl, (Endo et al 1988a), suggesting that HgCl, is absorbed by the mechanism of solvent drag. On the other hand, the increase in water absorption increased the absorption of HgCl, (Endo et al 1988a), suggesting that HgCl, is absorbed by the mechanism of solvent drag.…”
mentioning
confidence: 96%